Adaptation and validation of Confusion, Hubbub, and Order Scale in Mexican parents - Sánchez-Mondragón, Gabriela; Flores Herrera, Luz María (Acta Universitaria, 2019)
The socio-physical conditions of the family environment play a critical role in the child development and the processes generated within the household. In chaotic homes, negative effects have been found in child development and parental behavior; therefore, instruments to measure the environmental conditions in chaotic homes are needed. The aim of this study was to adapt and validate the Confusion, Hubbub, and Order Scale in Mexican parents. The participants were women and men from 19 to 49 years old (M= 31.0, SD= 6.31). Results indicate that the nine-item version possesses acceptable psychometric properties (Î±= 0.72). Empirical support was found for the structure of three factors (confusion, order and lack of routines) after the execution of the confirmatory factor analysis (Xi2 = 30.097, p = 0.18, RMSEA = 0.051).